Thermal degradation of poly[3-(1-cyclohexyl) azetidinyl methacrylate] - Coskun, M; Erten, H; Demirelli, K; Ahmedzade, M (Elsevier Sci Ltd, 2000)
Thermal degradation of poly[3-(1 -cyclohexyl)azetidinyl methacrylate] has been studied using a system consisting of a degradation tube, with a condenser for product collection of a gas phase IR cell and a rotary pump, and thermogravimetry (TG). Product analyses were performed by IR, GC-MS, H-1 NMR and C-13 NMR. Thermal degradation of the polymer begins at low temperature (about 180 degrees C) by decomposition of azetidinyl ring, producing some amine based products. The degradation produces anhydride ring structures in the chain above about 300 degrees C as a result of a reaction between two neighboring units. A mechanism of degradation showing the Formation of some products is discussed. (C) 2000 Published by Elsevier Science Ltd. All rights reserved.
Keywords: thermal degradation; cyclohexyl-azetidinyl methacrylate